Social Networking and Libraries: A Symbiotic Relationship - Dubey, Vipin (Journal of Advanced Research in Library and Information Science; Vol 11 No 1 (2024): Journal of Advanced Research in Library and Information Science, 2024)
Social networking platforms have revolutionized communication and information sharing, transforming how people interact, connect, and access resources. This article explores the intersection of social networking and libraries, examining the evolving role of libraries in the digital age and the opportunities and challenges presented by social media platforms. From enhancing community engagement to expanding outreach efforts and fostering collaboration, libraries are leveraging social networking tools to redefine their services and stay relevant in an increasingly interconnected world. This review delves into the multifaceted relationship between libraries and social media, highlighting the innovative ways in which libraries are harnessing the power of online platforms to engage with patrons, promote literacy, and build vibrant communities. Through case studies, best practices, and critical analysis, this article provides insights into the transformative potential of social networking for libraries and offers recommendations for maximizing its impact in the 21st century.